Electrochemical Behaviour and Sensing of Chlorpromazine at Polymer‐Free Kaolin‐Based Nanosodalite and Nanosodalite‐Graphene Foam Film modified Glassy Carbon Electrodes - Firmin Parfait Tchoumi; Cyrille Ghislain Fotsop; Guy Bertrand Tamne; Henrietta W. Langmi; Justin Claude Kemmegne‐Mbouguen; Emmanuel Ngameni (ChemElectroChem, 2024)
Abstract A nanosodalite (SOD) was synthesized utilizing Cameroonian kaolin and then used to prepare a nanocomposite (SOD‐GF) with graphene foam (GF). The as‐synthesized materials were characterized using X‐ray diffractometry (XRD), Fourier transform‐infrared (FT‐IR) spectroscopy, N2 adsorption‐desorption and scanning electron microscopy coupled with emission dispersive X‐ray (SEM/EDX). The results show a pure sodalite with high degree of crystallinity with crystallite size and BET surface area of 38.3 nm and 22 m2/g, respectively. The composite's characterization revealed a well‐integrated material in which the structural integrity of each material is maintained, its surface area being 4‐fold that of pristine SOD. Stable SOD and SOD‐GF modified glassy carbon electrode (GCE) were prepared by drop coating without a binder and utilized to study the electrochemistry of chlorpromazine (CPZ) in acidic, neutral and basic pHs. It appeared that (i) CPZ's electrochemical oxidation was a two‐step one‐electron process at SOD/GCE and a one‐step two‐electron process at SOD‐GF/GCE and (ii) the electrochemical reaction mechanism was an EEC mechanism at SOD/GCE while at SOD‐GF/GCE the mechanism was EEC at pH<4 and EC for greater pH. SOD/GCE and SOD‐GF/GCE were used to sense CPZ within CPZ's concentration ranging from 0.5‐30 μM with low detection limits.